Getting incentives right: Human capital investment and natural resource booms - Gerhard Toews; Alexander Libman (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2017)
The accumulation of human capital is usually considered an important corner stone in a country's economic development. While the use of resource rents to improve an educational system and, thus, increase the level of human capital appears to be an attractive option, resource rich economies frequently struggle with an efficient management of resource revenues. In this paper, we ask whether private individuals can at least partly compensate for government's failures by analysing the consequences of a resource boom on private demand for education. To do this we use the Household Budget Survey of Kazakhstan covering the period of 2001-2005. The oil boom provides us with the necessary exogenous variation to establish causality. We show that, in resource-rich districts of Kazakhstan, the resource boom increases the probability of employment in the formal sector for the educated labour force and the likelihood that households pay tuition fees for tertiary education. We are able to refute the conjecture that our effect is driven merely by the growing income of the households, by the growing supply of educational opportunities or by the immigration of educated households.
urn:nbn:de:101:1-2018061908283660069167
Keywords: Q33; I25; 330; Resource Booms; Education